2010
DOI: 10.1038/npp.2010.213
|View full text |Cite
|
Sign up to set email alerts
|

The Modulatory Role of the Lateral Septum on Neuroendocrine and Behavioral Stress Responses

Abstract: The lateral septum (LS) has been shown to have a key role in emotional processes and stress responses. However, the exact role of the LS on stress modulation is not clear, as previous lesion studies mostly used electrolytic lesions, thereby destroying the whole septal area, including medial components and/or fibers of passage. The aim of the present study was therefore, to investigate the effects of selective excitotoxic ablation of the LS on neuroendocrine and behavioral stress responses in rats. Bilateral ib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
99
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(105 citation statements)
references
References 83 publications
5
99
1
Order By: Relevance
“…Here evidence is reported of a brain system which, through modulation of GABA in the amygdala prefrontal cortical 5-HT, controls behavioral responses to stressful experiences sustaining immobility in the forced swimming paradigm that models depressive-like outcomes in rodents (Ebner et al, 2005(Ebner et al, , 2008Singewald et al, 2011). It was first demonstrated that, in mice, a stressful experience such as restraint induces a time-dependent increase of 5-HT output in the mpFC and of GABA in the BLA, in agreement with previous reports (Reznikov et al, 2009;Pascucci et al, 2009), and that selective depletion of cortical 5-HT canceled out these stress-induced responses, thus pointing to a controlling role of GABAergic transmission in amygdala by prefrontal 5-HT during stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here evidence is reported of a brain system which, through modulation of GABA in the amygdala prefrontal cortical 5-HT, controls behavioral responses to stressful experiences sustaining immobility in the forced swimming paradigm that models depressive-like outcomes in rodents (Ebner et al, 2005(Ebner et al, , 2008Singewald et al, 2011). It was first demonstrated that, in mice, a stressful experience such as restraint induces a time-dependent increase of 5-HT output in the mpFC and of GABA in the BLA, in agreement with previous reports (Reznikov et al, 2009;Pascucci et al, 2009), and that selective depletion of cortical 5-HT canceled out these stress-induced responses, thus pointing to a controlling role of GABAergic transmission in amygdala by prefrontal 5-HT during stress.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that 5-HT transmission in the mpFC is likely to engage GABA in the amygdala in stressful situations in order to determine coping outcomes. Here, using mice, it was attempted to assess whether amygdalar GABA regulation by prefrontal cortical 5-HT is a common neural substrate involved in processing stressful experiences and in determining active or passive coping behavior during forced swimming (Ebner et al, 2005(Ebner et al, , 2008Singewald et al, 2011). In particular, it was investigated whether 5-HT in prefrontal cortex is involved in brain response to uncontrollable stress through its modulating action on GABA in amygdala and whether these brain areas are part of a neural system necessary for the implementation of adaptive coping strategies.…”
Section: Introductionmentioning
confidence: 99%
“…The fish's dorsomedial (Dm) and dorsolateral (Dl) pallium have been characterised as functional homologues of the mammalian amygdala and hippocampus, respectively, and are implicated in stimuli salience, memory and learning (Goodson and Kingsbury, 2013;O'Connell and Hofmann, 2011;Vargas et al, 2009). Furthermore, in terms of stimuli salience and emotional coding, the mammalian lateral septum appears to work in conjunction with the amygdala and hippocampus to regulate emotional reactivity and goal-oriented behaviour, respectively (Luo et al, 2011;Singewald et al, 2011). The ventral part of the ventral telencephalon (Vv) in fish has been proposed as a putative homologue to the mammalian lateral septum (Goodson and Kingsbury, 2013;O'Connell and Hofmann, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This upregulation of the OTR was specifically localized in the amygdala, a region involved in stress and emotional regulation [25,26]. Therefore, this oxytocinergic system alteration may be involved in the modulation of long-term behavioural adaptations induced by chronic nicotine exposure.…”
Section: Discussionmentioning
confidence: 97%